The Effect of Gambir (Uncariae gambier) Extract Solution to the Quality of Fresh Catfish (Pangasius hypophtalmus) - Ronald Sohahau Manao; Edison '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The objective of this research was to determine the effect of gambir (Uncariae gambier)extract solution which different concentration to the quality of fresh catfish (Pangasiushypophtalmus). The method used in this research was experimental method, which usingblock random design (BRD). There were four levels of treatment in soaking of gambir extractsolution i.e. 0%, 15%, 20%, and 25%. The parameter observed were organoleptic value, pH,total plate count, and total volatile base. The result showed that the quality of fresh catfish(Pangasius hypophtalmus) without soaking gambir (Uncariae gambier) extract solution 0%was the best treatment by consumer acceptance, with pH 6.84, total plate count 1.1 x 104cfu/g, and total volatile base 21.22 mg N/100 g.Keywords : Fresh fish, gambir extract, Pangasius hypophtalmus, soaking, quality